The Relationship Between Peer Attachment and Psychological Well - Being Of University Students - Tyara Septiana Putri; Resnia Novitasari (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2017)
This quantitative study was aimed to determine the relationship between peer attachment and psychological well-being of university students. The subjects of this study were 69 university students from 20 to 29 years old. The measurements were Scale of Psychological Well-being (SPW; α = 0,805) based on six aspects of psychological well-being from Ryff & Keyes (1989) and Inventory of Parent and Peer Attachment (IPPA) subscale Peer Attachment (α = 0,903), scale was adapted based on three aspects from Armsden and Greenberg (1987). The results of this study showed a positive relationship between peer attachment and psychological well-being ofuniversity students, r = 0,382 and p = 0.001 (p<0.01). These findings suggest that psychological well-being was affected by peer attachment.  Key words: psychological well-being, peer attachment, university students